2008
DOI: 10.1097/yco.0b013e3282f32408
|View full text |Cite
|
Sign up to set email alerts
|

Major depression and comorbid substance use disorders

Abstract: Emerging results of recent studies comparing the outcome of major depressive disorder patients with comorbid major depressive disorder and substance use disorders suggest that there are fewer differential effects based on comorbidity than previously anticipated by older assumptions from smaller, less methodologically rigorous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
278
0
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(300 citation statements)
references
References 38 publications
10
278
0
12
Order By: Relevance
“…Alcohol and marijuana abuse are very common co-morbidities with major depression (Davis et al, 2008). Our analysis without these subjects demonstrated a similar result (reduced FA in the right ALIC) albeit non-significant.…”
Section: Tracts Of Alic In Depression and Diabetessupporting
confidence: 71%
“…Alcohol and marijuana abuse are very common co-morbidities with major depression (Davis et al, 2008). Our analysis without these subjects demonstrated a similar result (reduced FA in the right ALIC) albeit non-significant.…”
Section: Tracts Of Alic In Depression and Diabetessupporting
confidence: 71%
“…• Prior depressive episode (5) • Recent stressful life event (25,26) • Family history of major depression (5) • Chronic medical conditions (28,30,31) • Cognitive impairment or dementia (24,32) • Anxiety and substance abuse (28,33) • Multiple physical complaints, vague complaints or unexplained physical symptoms (21,31) For example, a patient who presents with persistent low mood and anhedonia associated with hopelessness and suicidal ideation for ten days (hence not fulfilling the criteria of at least two weeks) should be managed in the same way as a patient with major depression. In the DSM-5 (which replaces the DSM-IV) criteria, recent bereavement is now recognised as one of the stressors that can precipitate major depression; it is thus not an exclusion criterion for the diagnosis of major depression.…”
Section: Box 1 Persons At Risk Of Major Depression Include Those Withmentioning
confidence: 99%
“…(65,66) A useful method of differentiating major depression in medical patients, who may present with somatic symptoms similar to those found in major depression, is to ask about cognitive symptoms such as negative thinking, inappropriate guilt and low self-esteem. (67) Drugs and substance abuse Major depression is a risk factor for and is often associated with substance abuse, including that of alcohol, (33) which may be under-recognised in elderly patients. (68,69) In terms of lifetime prevalence, it has been shown that alcohol abuse is the second most common mental disorder among adults in Singapore.…”
Section: Other Organic Conditionsmentioning
confidence: 99%
“…Também é alta a prevalência de depressão maior na população jovem (10 a 29 anos): 22,3%. Esse achado corrobora resultados de estudos prévios, que evidenciam uma tendência de aumento na prevalência de depressão maior entre os jovens, provavelmente, refletindo a banalização do uso de substâncias psicoativas (DAVIS et al, 2008).…”
Section: Discussionunclassified